Mechanical, thermo-mechanical and thermal characteristics of multi-walled carbon nanotubes-added textile-reinforced composites. (November 2020) - Sezgin, Hande; Mishra, Rajesh; Militky, Jiri; Berk Berkalp, Omer
The influence of adding different types of multi-walled carbon nanotubes on mechanical (tensile strength and impact strength), thermo-mechanical (storage modulus, loss modulus and damping factor) and thermal properties (thermogravimetric and differential scanning calorimetry analysis) of fabric-reinforced polyester-based composite structures are analyzed in this study. Jute, E-glass and carbon fabrics are preferred as the reinforcement materials. Four-plied fabric-reinforced composites are fabricated using vacuum-assisted resin transfer molding technique. Results indicate that adding different types of multi-walled carbon nanotubes have increasing effect on mechanical and thermo-mechanical properties of composite structures; however, they have barely effect on thermal properties. Pristine multi-walled carbon nanotube-added specimens show higher mechanical and thermo-mechanical properties compared to functionalized multi-walled carbon nanotube-added samples.